2014
DOI: 10.1190/int-2014-0066.1
|View full text |Cite
|
Sign up to set email alerts
|

Geological and geophysical expression of a primary salt weld: An example from the Santos Basin, Brazil

Abstract: Primary salt welds form at the base of minibasins in response to complete evacuation of autochthonous salt. Analytical and numerical models suggest it is difficult to completely remove salt from a weld by viscous flow alone, which is especially true in multilayered evaporites, within which flow is likely heterogeneous due to lithologically controlled viscosity variations. Welds are important in the hydrocarbon industry because they may provide a hydrodynamic seal and trap hydrocarbons, or may allow transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 46 publications
5
42
0
2
Order By: Relevance
“…Our data, and that from the Campos (Wagner and Jackson, 2011) and Santos basins (Jackson et al, 2014), thus support the hypothesis of Wagner and Jackson (2011) that viscous flow is a good analytical approximation of the physical processes occurring during salt thinning and welding, but that viscous flow alone is unlikely to result in complete evacuation of a salt layer. However, it is important to note that a borehole, irrespective of the quantity and quality of data it provides, is only a 1D sample point; it is of course possible that, away from this sample point, the weld may be locally complete.…”
Section: The Geophysical and Geological Expression Of Salt Weldssupporting
confidence: 78%
See 2 more Smart Citations
“…Our data, and that from the Campos (Wagner and Jackson, 2011) and Santos basins (Jackson et al, 2014), thus support the hypothesis of Wagner and Jackson (2011) that viscous flow is a good analytical approximation of the physical processes occurring during salt thinning and welding, but that viscous flow alone is unlikely to result in complete evacuation of a salt layer. However, it is important to note that a borehole, irrespective of the quantity and quality of data it provides, is only a 1D sample point; it is of course possible that, away from this sample point, the weld may be locally complete.…”
Section: The Geophysical and Geological Expression Of Salt Weldssupporting
confidence: 78%
“…For example, low viscosity, more mobile lithologies, such as halite and potash salt, occurring in thick autochthonous salt in sufficiently large quantities, may be 11 preferentially expelled from thinning salt before relatively high viscosity, less mobile lithologies, such as carbonate, anhydrite and sandstone. As such, during welding, salt becomes relatively enriched in these less mobile, non-halite/potash salt lithologies, which, due to the effects of boundary drag along the upper and lower salt contacts, becomes trapped in the weld as the salt thinned (compare 'differential purification by movement'; Kupfer, 1968;see also Wagner andJackson, 2011 andJackson et al, 2014).…”
Section: Composition Of Salt Weldsmentioning
confidence: 99%
See 1 more Smart Citation
“…1a). Several studies have documented geologic attributes of these welds and their importance to hydrocarbon exploration (Hoetz et al, 2011;Jackson et al, 2014;Maione, 2001;Peel, 2014;Rowan et al, 2012;Wagner, 2010). For instance, Hoetz et al (2011) studied the data from wells drilled through horizontal welds and found a consistent reduction in the porosity of sediments near the welds.…”
Section: Introductionmentioning
confidence: 97%
“…Zechstein Supergroup control the structural styles that develop during Middle Jurassic-to-Early Cretaceous 492 rifting (see also Lewis et al, 2013;Jackson and Lewis, 2016). Diapirism is common in hangingwall basins, 493 where autochthonous salt was thick and halite-rich (e.g.…”
mentioning
confidence: 99%